Ask your own question, for FREE!
Puzzles & Challenges
mhchen:

What's wrong with this proof: Suppose a = b. Then: a^2 = ab | Multiply by a (a^2) - (b^2) = ab - (b^2) | Subtract (b^2) (a+b)(a-b) = (a-b)b | Factor a+b = b | Divide by (a-b) b + b = b | Substitute a = b 2b = b | Addition 2 = 1 | Divide by b

1 month ago
Vocaloid:

both of the division steps. you can't divide by (a-b) since a - b is 0 according to the original statement a = b you also cannot divide by b unless you stipulate that b =/= 0

1 month ago
Can't find your answer? Make a FREE account and ask your own question, OR you can help others and earn volunteer hours!